Comparative morphological characteristics of the uteroplacental area in abnormal placentation - I. A. Kulikov; N. V. Nizyaeva; T. V. Sukhacheva; R. A. Serov; N. B. Tikhonova; T. V. Fokina; A. P. Milovanov; T. N. Belousova; E. R. Milyutina; L. M. Mikhaleva (Acta Biomedica Scientifica, 2023)
The aim. To carry out a comparative morphological characteristic of the uteroplacental area with abnormal placentation – pl. accreta, pl. increta, pl. percreta. Materials and methods. The study included 47 patients with atypical placentation; the comparison group included 10 healthy pregnant women with uterine scar after a previous caesarean section. A histological study of uteroplacental area samples was performed with hematoxylin and eosin, methylene blue staining. An immunohistochemical study with primary antibodies to cytokeratin 7 (CK7), Hif2a, vascular endothelial growth factor, α-SMA was carried out. The differences between the compared values were considered to be statistically significant at p < 0.05. The results of the study. Pl. accreta was determined in 12 (25.5 %), pl. increta – in 30 (63.9 %), pl. percreta – in 5 (10.6 %) patients. In all patients of the main group, the decidua was completely or partially absent in the area of abnormal placentation or was replaced by an uneven layer of fetal fibrinoid. Cases when placental villi unevenly penetrated into the thickness of myometrium in the form of “tongues” or “coves” bordered by fetal fibrinoid and often located intermuscularly were defined as pl. increta (n = 26). Cases with the placental villi ingrowth to the serous membrane were considered as pl.  percreta (n  =  5). In cases with deep variants of  ingrowth (pl. increta and pl. percreta) (n = 31), the villi were visualized in the lumen of the vessels and the thinning of the lower uterine segment with the presence of stretched muscle bundles was revealed. Aseptic necrosis of  the myometrium was  found: in 2 (16.7 %) of 12 women with pl. accreta, in 26 (86.7 %) of 30 women with pl. increta and in 5 (100 %) women with pl. percreta. There were no areas of necrosis in the myometrium of the women of comparison group. Conclusion. The appearance and increase of myometrial necrosis zones in response to an increase in the depth of placental villus ingrowth were detected. Myometrial necrosis zones could be the cause of activation of angiogenic factors and an important stimulus for the development of abnormal vascularization in placenta accreta spectrum.